Evaluation of the adequacy and diagnostic accuracy of the histology samples obtained with a newly designed 19-gauge EUS histology needle - Julio Iglesias-García; Ihab Abdulkader; Jose Lariño-Noia; J. Enrique Domínguez-Muñoz (Revista Espanola de Enfermedades Digestivas, 2014)
Background: Endoscopic ultrasound (EUS)-guided fine needle aspiration (FNA) is an accurate technique for sampling intraintestinal and extraintestinal lesions. However, cytology possesses certain limitations, which may be overcome if histological specimens are provided to the pathologist. Aim: The aim of the study was to evaluate the accuracy of a newly developed 19G histology needle. Methods: Retrospective analysis of a prospectively collected data base including patients who underwent EUS-guided biopsy with the 19G ProCoreTM histology needle for the evaluation of intraintestinal or extraintestinal lesions. Samples were obtained after one needle pass, recovered into ThinPrep® and processed for histological analysis. Results were compared to the gold standard of surgical histopathology, or global pathological, clinical and radiological assessment, and follow-up in non-operated cases. Results are shown as mean ± SD. Percentage of optimal samples for histological evaluation and the overall diagnostic accuracy were evaluated. Results: 87 patients (mean age 62.9 years, range 25-88 years, 36 woman) were included. Lesions mean size was 41.6 ± 21.3 mm. 66 lesions (75.9 %) were considered as malignant and 21 (24.1 %) as benign. EUS-guided biopsy was feasible in all cases (100 %). Sample quality was adequate for histological assessment in 82 lesions (94.2 %). In the remaining cases the sample was adequate for cell-block evaluation. Sensitivity, specificity, PPV, NPV, and overall accuracy for malignancy were 93.4 %, 100 %, 100 %, 84 %, and 95.4 %, respectively. There were no complications related to the procedure. Conclusion: The EUS-guided biopsy with the 19G histology needle provides with an optimal core sample for histological evaluation allowing a high histopathologic diagnostic accuracy.